Real-time control of activated sludge process - Chen, Chung Yuan. (2008)
The main objective of this project is to develop an appropriate theory to describe the response of an activated sludge (AS) system under shock loading. Secondly, a computer program is to be developed which is capable of simulating the performance of an AS process.